A Systematic Literature Review of the Antecedents and Consequences of Relationship Quality in Online Activity Context - Ardy Wibowo (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Relationship quality is widely practiced across many business and marketing research. In the online activity context, relationship quality is an important thing to maintain the relationship among the customer and service provider because of the lack of face-to-face interaction, uncertainty, and intangibility. Understanding what is the antecedents and consequences that conceptualize into relationship quality construct can guide the researcher to design an analytical framework or model to achieve high-quality research paper in the future. This study reviewed 21 studies in the recent 10 years and find out 29 antecedents and 12 consequences of relationship quality that exhibits significant relationships. Finally, the article concluded the conclusions and future research direction.